The effect of a limited number of projections and reconstruction algorithms on the image quality of megavoltage digital tomosynthesis - Sarkar, Vikren (J Appl Clin Med Phys, 2009)
In order to investigate the effect of the number of projections on digital tomosynthesis image quality, images were acquired over a 40 degree arc and sampled into sets of 2 to 41 projections used as input to three different reconstruction algorithms: the shift‐and‐add, the Feldkamp‐Davis‐Kress filtered back projection algorithms, and the simultaneous algebraic reconstruction technique. The variation of several image characteristics, such as in‐plane resolution, contrast to noise ratio, artifact spread, volumetric accuracy, and dose, are investigated based on the reconstruction algorithms used and also the number of projections used as source data. The results suggest that only 11 projections are required since the various parameters checked do not improve much past that number. As a reconstruction algorithm, SART did best but took much longer to reconstruct images. Thus, if reconstruction time is a determining factor, filtered back‐projection looks like a better compromise. PACS number: 87.57.C‐, 87.57.nf, 87.57.Q‐, 87.59.‐e